CHANGES IN THE DEMOGRAPHIC AND CLINICAL PROFILE OF PATIENTS AND THE STRUCTURE OF HIGH-TECH OPHTHALMOLOGICAL CARE FOR DIABETIC RETINOPATHY - Ismayilov, G.M. (World of Medicine and Biology, 2023)
Two samples of 250 patients with diabetic retinopathy were retrospectively formed before the introduction of compulsory health insurance (2018–2019) and after it (2021–2022). For all patients, standard information was collected, which included data on gender, age, type and duration, as well as treatment options for diabetes mellitus, the stage of diabetic retinopathy (non-proliferative, preproliferative, proliferative), form (exudative, edematous, ischemic) and type (focal, diffuse, cystic and cystic with the presence of vitreoretinal fractions) maculopathy, as well as comorbid eye pathologies (secondary glaucoma, cataracts, age-related macular degeneration, vitreous diseases and others). A comparison of the treatment results in the clinic before and after the introduction of compulsory health insurance shows that the difference between them is also statistically significant (p
Keywords: diabetic retinopathy; compulsory health insurance; maculopathy; laser coagulation